STUDI STATUS STOK DAN TINGKAT EKSPLOITASI KEPITING BAKAU DI DESA MUARA KEMBANG KECAMATAN MUARA JAWA KALIMANTAN TIMUR - Ginting, Rozi syah putra; Eryati, Ristiana; Nurfadilah (Department of Aquatic Resources Management, Faculty of Fisheries and Marine Science, Mulawarman University, 2024)
Excessive harvesting of mangrove crabs of all sizes and those with mature gonads will disrupt the ecosystem of mangrove crabs. Therefore, this research was conducted to determine the stock status and exploitation level of mangrove crabs. The research was conducted in Muara Kembang Village, Muara Jawa District, East Kalimantan Province The research was carried out in April 2023, and 150 mangrove crabs were randomly sampled Quantitative data from the measurement and observation of the sex of mangrove crabs were processed using the FISAT II application. The measurement of crab shells and observations of mangrove crabs resulted in total mortality (Z) of mangrove crabs, which is 301/year for males and 068/year for females The highest age group of mangrove crabs at 1 year old reached a length range with an average length of 1306 mm for males and 1070 mm for females. Mortality of capture (F) of mangrove crabs is 203 in males and 088 in females and the natural mortality (M) in males is 097 and in females is 078 The exploitation rate of male mangrove crabs obtained a value of 067 (high) while in female mangrove crabs it is 053 (normal)